THE STUDY OF SOCIAL IMPACT ASSESSMENT OF PEOPLE MODERN TOURISM MANAGEMENT: A CASE STUDY OF AYUTTHAYA HISTORICAL PHRANAKON SI AYUTTHAYA PROVINCE - Krachaechan, Chanidapa (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
This research ha a purpose to study social conditions, social impact and guidelines to determine the solution of social impacts from modern tourism management, a case study of the Ayutthaya Historical Park, Phra Nakhon Si Ayutthaya province by using quantitative research method and qualitative research method. In the field of quantitative research, the researcher collected the information from questionnaires for the sample of 400 households. The obtained data were analyzed by using descriptive statistics and mean comparison. For qualitative research, the data were collected by using structured interviews with three key informants and analyzed with descriptive analysis. The study found that the sample group had a positive opinion on the social impact at very good level in both economic and social aspects. This was due to the fact that tourists will spend a lot of money on tourism since renting accommodation, buying food to buying souvenirs in each of their travelling. Such activities can be assummed as the ways to support the villagers in that area to earn more income and have a better life. However, considerin the environmental impact, it was found that the problem of waste is increasing including the problem of traffic jams around the entrance route to tourist attractions as well as the problem of tourist attractions degradation. The recommendations from the research are that the government should focus on education and cultivate the consciousness of the people in the country for the development of conservation tourism ny inserting the development of ecotourism into the curriculum at all levels including encourage the launch of a course on the development of ecotourism at the tertiary level.